Healthcare Systems Strengthening in Smaller Cities in Bangladesh: Geospatial Insights From the Municipality of Dinajpur - Shaikh Mehdi Hasan; Kyle Gantuangco Borces; Dipika Shankar Bhattacharyya; Shakil Ahmed; Azam Ali; Alayne Adams (SAGE Publishing, 2020)
Throughout South Asia a proliferation of cities and middle-sized towns is occurring. While larger cities tend to receive greater attention in terms national level investments, opportunities for healthy urban development abound in smaller cities, and at a moment where positive trajectories can be established. In Bangladesh, municipalities are growing in size and tripled in number especially district capitals. However, little is known about the configuration of health services to hold these systems accountable to public health goals of equity, quality, and affordability. This descriptive quantitative study uses data from a GIS-based census and survey of health facilities to identify gaps and inequities in services that need to be addressed. Findings reveal a massive private sector and a worrisome lack of primary and some critical care services. The study also reveals the value of engaging municipal-level decision makers in mapping activities and analyses to enable responsive and efficient healthcare planning.